AVOIDING DEATH BY POWERPOINT. - Ball, Corbin (Public Management (00333611), 2009)
The article provides information how to manifest creative computerized presentation program using PowerPoint software. The author emphasizes some important factors based from the experiences he encountered such as number of words limitation, application of wireless advance technology and proper applications of other special features of the program. He recommends to use some alternative Web site technologies like Palm emulators, flash animation and streaming video.